Structure and Manning of the Planning Commission Report of the Task Force - Planning Commission (Planning Commission Government of India, 1989)
The Planning Commission Task Force Report, chaired by Shri V. Krishnamurthy, evaluates the relevance, structure, and functions of India’s Planning Commission in the context of a market-oriented, deregulated economy. The report emphasizes that despite reduced public sector involvement, the Commission remains critical for long-term economic analysis, policy coordination, and resource allocation. It recommends a streamlined organizational structure with six focused divisions—Macro-Economic and Perspective Planning; Agricultural and Rural Development; Infrastructure, Industry, and Trade; Human Resources Development and Social Infrastructure; Science and Technology; and State Plans and Support Systems. Key reforms include concentrating on strategic analyses, centralizing project appraisal functions, restructuring the Planning Evaluation Organisation for better impact assessment, and establishing a professional workforce of approximately 450 experts supported by flexible recruitment and career development mechanisms. By enhancing its role as a “Think Tank,” fostering inter-disciplinary collaboration, and facilitating consistent engagement with policymakers, the Task Force aims to modernize the Planning Commission, ensuring its continued relevance and effectiveness in India’s evolving economic landscape.
Government of India Planning Commission
Keywords: Task Force; Economic Planning; Deregulated Economy; Long-Term Strategy; Resource Allocation; Perspective Planning; Investment Strategy; Organizational Restructuring; Human Resource Development; Policy Coordination; Think Tank